Bacterial species and forms of resistance of intestinal parasites found in collectives of the city of Divinópolis - MG - A. G. Parreira; J. J. N. Melo; R. A. Almeida; T. Filippis (Scientific Electronic Archives, 2019)
Public transportation buses are places of intense movement of people, which may constitute important dispersal vehicles of microorganisms and parasites. In such context, this paper sought to assess the microbial and parasitological diversity inside urban and periurban buses that run four routes in Divinópolis MG. For the microbial study, 80 sample collections were  made by using a sterile swab containing Stuart transport medium and were taken to the Microbiology Laboratory of the UEMG – Divinópolis MG, in order to perform the laboratorial tests. For search about eggs and cysts of intestinal parasites, 80 samples were  collected, out of which 40 were collected by using the Graham method, and 40 were collected by using swab. Two smears of each sample were analyzed.  In the microbial research, 1097 CFU mL-1 of heterotrophic bacteria were analyzed.  Through mass spectrometry eleven potentially pathogenic species of bacteria were identified out of which seven were identified as antibiotics-resistant.  In the parasitological analysis through the Graham method a probable cyst of Blastocystis hominis and an egg similar to those of Hymenolepis sp. were identified. Through the use of swab four eggs similar to those of Ascaris sp. and a probable cyst of B.hominis were also identified. The bacterial and parasitological prevalence was higher on buses that run in hospital and periurban areas. Based on results obtained it was possible to outline a profile until then unknown of the bacteria and parasites present in some of the main public transportation routes of Divinópolis MG.